Maternal tributyrin supplementation in late pregnancy and lactation improves offspring immunity, gut microbiota, and diarrhea rate in a sow model - Lin, Yan; Li, Dan; Ma, Zhao; Che, Lianqiang; Feng, Bin; Fang, Zhengfeng; Xu, Shengyu; Zhuo, Yong; Li, Jian; Hua, Lun; Wu, De; Zhang, Junjie; et al. (Frontiers in Microbiology, 2023)
Introduction Several studies have evaluated the effects of tributyrin on sow reproductive performance; however, none of these studies have investigated the effects of tributyrin on sow gut microbiota and its potential interactions with immune systems and milk composition. Therefore, we speculated that tributyrin, the combination of butyrate and mono-butyrin without odor, would reach the hindgut and affect the intestinal microbiota composition and play a better role in regulating sow reproductive performance, gut flora, and health. Methods Thirty sows (Landrace × Yorkshire) were randomly divided into two groups: the control group (CON) and the tributyrin group (TB), which received basal diet supplemented with 0.05% tributyrin. The experimental period lasted for 35 days from late pregnancy to lactation. Results The results showed that TB supplementation significantly shortened the total parturition time and reduced the diarrhea rate in suckling piglets. On day 20 of lactation, the milk fat and protein levels increased by 9 and 4%, respectively. TB supplementation significantly improved the digestibility of dry material, gross energy, and crude fat in the sow diet, but had no significant effect on crude protein digestibility. Furthermore, TB supplementation increased the levels of IL-10, IL-6, and IgA in the blood of weaned piglets, but had no effect on maternal immunity. Analysis of the fecal microbial composition revealed that the addition of TB during late gestation and lactation increased the microbiota diversity in sows and piglets. At the phylum level, sows in the TB group had a slight increase in the relative abundance of Bacteroidota and Spirochaetota and a decrease in Firmicutes. At the order level, the relative abundance of Lactobacillales was increased in piglets and sows, and the TB group showed increased relative abundance of Enterobacterales and significantly decreased relative abundance of Oscillospirales in piglets. At family level, the relative abundance of Lactobacillaceae, Oscillospiraceae, and Christensenellaceae increased in sows, and the relative abundance of Enterobacteriaceae and Lactobacillaceae increased in piglets. At genus level, the relative abundance of Lactobacillus increased in sows and piglets, but the relative abundance of Subdoligranulum and Eubacterium_fissicatena_group decreased in piglets in the TB group. Discussion In conclusion, tributyrin supplementation shortened the farrowing duration and reduced the diarrhea rate of piglets by improving the inflammatory response and composition of gut microbiota in piglets and sows.